Intravenous Immunoglobulin and Immunomodulation of B-Cell – in vitro and in vivo Effects - Mitrevski, Milica; Marrapodi, Ramona; Camponeschi, Alessandro; Cavaliere, Filomena Monica; Lazzeri, Cristina; Todi, Laura; Visentini, Marcella (Frontiers in Immunology, 2015)
Intravenous immunoglobulin (IVIG) is used as replacement therapy in patients with antibody deficiencies and at higher dosages in immune-mediated disorders. Although different mechanisms have been described in vitro, the in vivo immunomodulatory effects of IVIG are poorly understood. Different studies have suggested that IVIG modulates B cell functions as activation, proliferation and apoptosis. Recently, it was shown that IVIG induces in vitro B cell unresponsiveness similar to anergy. In accord with this, we recently reported that IVIG therapy in patients affected by common variable immunodeficiency (CVID) interferes in vivo with the B cell receptor (BCR) signalling by increasing constitutive ERK activation and by reducing the phosphorylated ERK increment induced by BCR cross-linking. Moreover we observed that IVIG induces in CVID patients an increase of circulating CD21low B-cells, an unusual population of anergic-like B cells prone to apoptosis. Therefore IVIG at replacement dose in vivo could prime B cells to an anergic, apoptotic program. Here we discuss these recent findings, which may improve our understanding of the immunomodulatory effects of IVIG, individualizing single involved molecules for more specific treatments.